Na busca dos novos líderes: o processo de construção de candidaturas ao legislativo municipal – aspectos teóricos e um estudo de caso - Marques, José Elias Domingos Costa (Universidade Federal de São Carlos, 2007)
This article subjects, under the prism of the neo-institutionalism studies, analyze the process of building of candidacies to the municipal legislative, which the political parties has an important paper in this process while institutional agents of control above the career policy. The research adopts the prospect of the rational choise to show the candidate as being result from the political encompassing the leaderships parties. The dissertation bodywork shares in two parts: one involving a theory work, approaching the most important researches about the subject; and like a case work, beyond a study of the candidate selection process on the two most important political parties of São Carlos city, during last two municipal elections (2000 and 2004).
Keywords: Ciência política; Novo institucionalismo; Seleção de candidatos; Recrutamento político; Carreira política; CIENCIAS SOCIAIS APLICADAS